CHARACTER DEVELOPMENT OF FLORENTINO ARIZA AS SEEN IN GABRIEL GARCIA MARQUEZ’S LOVE IN THE TIME OF CHOLERA - Mala Hernawati (Universitas Gadjah Mada, 2013)
Florentino Arriza is the main character in Gabriel Garcia Marquez’s novel, Love in the Time of Cholera. This main character experiences the change from an innocent young man to become an indecent man. This change is mainly caused by his love to a woman named Fermina Daza. Destiny makes him wait for more than half a century to finally win her love. This article results in several conclusions. First, Florentino Ariza fits the criteria of the combination of the dynamic and round characters. Second, he belongs to the group of Melancholy. In addition, there are two factors for his personality changes: lovesickness and environmental temptation.